Consumer attitudes towards the health benefits of 100% fruit juice in South Africa - Dr RG Duffett (The Retail and Marketing Review, 2018)
The health effects of 100% fruit juice have received widespread attention from both scientific and public forums. However, much of this literature has placed emphasis on the possible negative health risks of consuming pure (100%) fruit juice (PFJ). This research aims to explore South African consumers’ attitudes towards the health benefits of PFJ, as well as determine if various consumption and socio-demographic factors have an association with consumers’ attitudes. The study included 7 640 fruit juice consumers from cross-sectional research conducted in South Africa by means of a survey. The data was examined via a generalised linear model, which employed analysis of variance via Wald’s Chi-square statistic distribution. A majority of participants were in agreement that PFJ held a number of health benefits. Heavy PFJ consumers and those that purchased fruit juice with the greatest frequency perceived more favourable health benefits than consumers who purchased and consumed PFJ with lower regularity. Female consumers who completed higher education levels; were of the Black population group; and came from high income groups displayed favourable attitudes regarding PFJ health benefits. The research shows that consumers have positive attitudes towards the health benefits of 100% fruit juice regardless of the ubiquitous negative press. However, several consumption (drinking and purchase incidence; time-of-day; and reasons for consumption) and sociodemographic (gender, education level and population group) variables had either positive or negative associations with consumers’ attitudes.